Mednarodno prostovoljno delo - Razpotnik, Barica (Geografski obzornik, 2006)
International voluntary work is becoming more accessible and thus more populardue to the huge variety of short- and long-term projects, involving several thousand participants each year. It has a great impact on the hosting community and the volunteers themselves.
Keywords: prostovoljno delo; student; študenti; mladi; Europe; Evropa; Islandija; Finska; mölkky